If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -2x = 7 + 2x + -6 Reorder the terms: 9 + -2x = 7 + -6 + 2x Combine like terms: 7 + -6 = 1 9 + -2x = 1 + 2x Solving 9 + -2x = 1 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9 + -2x + -2x = 1 + 2x + -2x Combine like terms: -2x + -2x = -4x 9 + -4x = 1 + 2x + -2x Combine like terms: 2x + -2x = 0 9 + -4x = 1 + 0 9 + -4x = 1 Add '-9' to each side of the equation. 9 + -9 + -4x = 1 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = 1 + -9 -4x = 1 + -9 Combine like terms: 1 + -9 = -8 -4x = -8 Divide each side by '-4'. x = 2 Simplifying x = 2
| 10=2(y-4)+4 | | 56=c+24 | | -8(4b+3)+(33b-7)=0 | | 7x-9=3(x+5) | | 1.3x-2.39=5.67x+4.74 | | b+5=-10 | | .75a-.666=.583 | | 3(4-5k)-5(7-2k)+6=3k+7 | | .3333333334z-4=-.3333333334z+18 | | z^2+9z-9=(2z+3)(z-3) | | 2v^3-3v^2-14v+21=0 | | 6(x-3)=2x+4-6 | | 4-49v^2=0 | | -3/4+(-3/4)=0 | | -6x+16=-2x | | .5d=2-.5d | | 2/5+1/5=0 | | 4.8q-5.9-5.7q=-1.9q-4.2 | | 1.3p+0.3p-2=1.2 | | 15a^2+a=2 | | 4(4x-5)= | | 9x^2+15x+52=352 | | 2x^2+3y^2-2xy=10 | | 7y^2+23y=20 | | 8(2+x)=3x-14 | | 108-2x=34x+20 | | 3(z-7)=18 | | 30v^3x^9+9v^2x^6y^4=0 | | 6-3(3x-2)=-6 | | 3(2-7)=18 | | 5x-(2x+12)=3(x-4) | | 6(.5b+3)+4(12-b)=0.83 |